KADAR BILIRUBIN PASCA FOTOTERAPI PADA BAYI DI RSIA FATMA BOJONEGORO. - Siti Istiqomah; Budi - Santosa (LPPM Universitas Abdurrab, 2023)
One phenomenon that is still often found in newborns is the occurrence of hyperbilirubinemia. Phototherapy is one treatment to avoid a more fatal condition. The aim of this study was to see the effect of phototherapy on total bilirubin levels in infants with hyperbilirubinemia. The Study used Observational analytic research methods were carried out in a population of infants who experienced jaundice at RSIA Fatma Bojonegoro. The sampling technique is a total population of 110 respondents through medical record data. data in the form of respondent characteristics, phototherapy, and bilirubin levels were presented through univariate and bivariate analysis. The results showed that the bilirubin level in infants with hyperbilirubinemia after phototherapy decreased by an average of 3.086 mg/dL. Nonparametric statistical test results with 2 related samples obtained a significance degree value of Ï (0.000) < Î± (0.05) Ha was accepted, meaning that there was an effect of phototherapy on reducing total bilirubin. levels in babies. Based on the result stydy, that phototherapy has a significant effect on reducing total bilirubin levels in hyperbilirubinemia infants.